2015
DOI: 10.29037/ajstd.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Palm (Elais guineensis) Fruit Extracts on Glucose Uptake Activity of Muscle, Adipose and Liver Cells

Abstract: The effect of oil palm (Elaeis guineensis) fruit aqueous extract (OPF) on glucose uptake activity of three different cell lines was investigated. The cell lines were incubated with different concentrations of OPF to evaluate the stimulatory effect of OPF towards glucose uptake activity of L6 myotubes, 3T3F442A adipocytes and Chang liver cell line. The glucose uptake activities of all tested cells were enhanced in the presence of OPF extract (basal condition). Nevertheless in combination of OPF extract and 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…GLUT4 and AMPK were related by a mechanical pathway starting with the activation of AMPK by polyphenols and resulting in the induction of GLUT4 transporters translocation [ 52 , 59 61 ]. The addition of insulin enhanced the effect of DSE on GLUT 4 level but not on AMPK level, which indicated that DSE could also translocate GLUT4 via the direct insulin-dependent mechanism, inducing the translocation of GLUT4 transporters [ 51 , 62 , 63 ]. AMPK is well-known to work as an energy sensor [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…GLUT4 and AMPK were related by a mechanical pathway starting with the activation of AMPK by polyphenols and resulting in the induction of GLUT4 transporters translocation [ 52 , 59 61 ]. The addition of insulin enhanced the effect of DSE on GLUT 4 level but not on AMPK level, which indicated that DSE could also translocate GLUT4 via the direct insulin-dependent mechanism, inducing the translocation of GLUT4 transporters [ 51 , 62 , 63 ]. AMPK is well-known to work as an energy sensor [ 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%